Perilaku Kepemimpinan Instruksional Dan Dampaknya Terhadap Pengajaran Guru Dikelas (Lembaga Pengembangan Kinerja Dosen, 2025)
The theory of quality teachers asserts that they must demonstrate professional teaching performance. With strong performance, the overall quality of the school will also improve, positively impacting student achievement. Efforts to enhance teachers' teaching performance can be carried out through the implementation of instructional leadership by the school principal. This article aims to examine the influence of instructional leadership on teachers' teaching performance. Instructional leadership can create a school climate that aligns with teachers’ learning needs. Principals who apply instructional leadership do not hinder teachers from developing and improving their skills in carrying out their roles as educators. Instructional leadership is essential and should be practiced by all school principals who seek to bring about improvements in teachers' teaching performance.